Lexeme in a traditional dictionary and an electronic lexical database - Murmulaitytė, Daiva (Lietuvių kalba, 2010)
Traditional dictionaries provide lexicographic data of the same type in different ways; such unrestricted freedom might result in imprecise information. Some such cases are explained by an attempt to compile traditional dictionaries so that they are handy for their users. The paper discusses several non-systemic cases of providing forms of lexicographic items, their meanings and shades of meaning, derivatives, proper and common lexis. The data has been drawn from more than ten dictionaries of several languages. The structure of the electronic database requires utmost precision; therefore, any non-systemic items are not justified. Due to the above reasons, a lexeme, or a lexicographic unit in one of its meanings, has been chosen as the key structural unit of the Database of Contemporary Lithuanian Lexicon (DCLL, Dabartinės lietuvių leksikos duomenų bazė). To produce a most precise card of a lexeme is much more rational and simpler than that of the whole lexicographic unit. In the process, a number of analogous cases and other cases of non-systemic description of data should be taken into account. Moreover, it is hardly possible to consider them all. Thus an attempt will be made to finally produce the DCLL as a card index of lexemes rather than lexicographic units (their entries). Dictionary entries are to be produced by joining the lexemes automatically.
Keywords: none